«THE DESERT FATHERS AND THE WOMEN UNDEFILED...» - R. B. Semevsky (Труды по прикладной ботанике, генетике и селекции, 2018)
Participation of scientists from VIR in a rally race through the territory with complex soil composition provided valuable contribution to the development of land use and applied geosciences.